RENDS: How internet search undermines the validity of political knowledge measures - Smith, B. Clifford, S. and Jerit, J. (Political Research Quarterly)
Political knowledge is central to understanding citizens$1 (Bengagement with politics. Yet, as surveys are increasingly conducted online, participants$1 (Bability to search the web may undermine the validity of factual knowledge measures. Recent research shows this search behavior is common, even when respondents are instructed otherwise. However, we know little about how outside search affects the validity of political knowledge measures. Using a series of experimental and observational studies, we provide consistent evidence that outside search degrades the validity of political knowledge measures. Our findings imply that researchers conducting online surveys need to take steps to discourage and diagnose search engine use.- Reproduced s
Keywords: Political knowledge, Online surveys, Validity